Analisis dan Implementasi Sistem Informasi Akuntansi Menggunakan Metode Accrual Basis (Studi Kasus: CV Satu Holiday Tour dan Travel Bandung) - Rikky Wisnu Nugraha; Yumma Cahya Dwiana (Jurnal Akuntansi)
CV Satu Holiday Tour and Travel is a servicencompany engaged in the travel agency. In managing, calculating and recording transactions at CV Satu Holiday, it is still done using a cash book and in making financial reports using a spreadsheet, as well as in accounting records that the company does not fully describe the assets, liabilities, and equity of the company. The purpose of thisfresearch is to implement a system that can help manage accrual-based financial records. This study uses a descriptive method to describe a situation or event that produces the meaning and implications of a problem to be solved. By doing several stages of analysis to describe the system and implement the accounting module Odoo software in the company. The results ofnthe implementation of an accounting informationlsystemnusing the Odoo software accounting module in the company can facilitate work in the process of recording accrual transactions and making accrual-based financial reports that can be presented more quickly, completely and accurately. This research is expected to be used as knowledge and reference material regarding the implementation of accrual-based financial transaction recording using Odoo software with accounting modules and can be developed and integrated with other modules. Keywords:Accounting Information System, Accrual Basis, software Odoo, Accounting Module